2008
DOI: 10.1166/jnn.2008.151
|View full text |Cite
|
Sign up to set email alerts
|

Thickness Dependent Structural, Electronic, and Optical Properties of Ge Nanostructures

Abstract: In the present paper, we have investigated structural, optical as well as electronic properties of electron beam evaporated Ge thin films having layer thicknesses ranging from ultra-thin (5 nm) to thick (200 nm). The Raman spectra show that all peaks are shifted towards lower wave number as compared to their bulk counterparts and are considered as a signature of nanostructure formation and quantum confinement effect. The Raman line exhibits transformation from nanocrystalline to microcrystalline phase with a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…This pronounced effect may be due to TiO 2 in the multilayer films that tend to isolate Ge crystallites/islands and layers from each other for enhanced quantum confinement effects. It is well-known that threedimensional quantum confinement in nanoparticles is much more effective that one-dimensional quantum confinement in 2-D layers [14]. The pronounced increase with annealing in our multilayer films seems to arise from gradual conversion of 2-D layers into 3-D islands, crystallites, or quantum dots partly isolated from each other by TiO 2 .…”
Section: Optical Studiesmentioning
confidence: 70%
See 4 more Smart Citations
“…This pronounced effect may be due to TiO 2 in the multilayer films that tend to isolate Ge crystallites/islands and layers from each other for enhanced quantum confinement effects. It is well-known that threedimensional quantum confinement in nanoparticles is much more effective that one-dimensional quantum confinement in 2-D layers [14]. The pronounced increase with annealing in our multilayer films seems to arise from gradual conversion of 2-D layers into 3-D islands, crystallites, or quantum dots partly isolated from each other by TiO 2 .…”
Section: Optical Studiesmentioning
confidence: 70%
“…Vapor-deposited Ge films exhibit higher band gap energy [14,15,19], in comparison with bulk Ge ($0.7 eV). Gorokhov et al [15] have found that higher band gap energy is due to small particle size of Ge crystals isolated by a minute amount of oxide.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations